Aclimatização de mudas de café oriundas de embriões zigóticos: Aproveitamento de sementes envelhecidas - Vilela, Ana Luiza de oliveira (2020)
Coffee is one of the most important products on the world market, Brazil is the largest producer and exporter of this commodity, whose propagation is still carried out by seedlings produced from seeds. However, there is a loss of seed viability in a few months after harvest. One of the factors that may interfere with the germination and emergence of coffee seeds is the endosperm, rich in phenolic substances that can influence the embryo's growth process. Excision of the embryo from the seed and subsequent cultivation in vitro would eliminate the problem of oxidation by this type of compound. However, a substantial number of plants in vitro do not survive the transfer to greenhouse or growth chamber conditions. Most species grown in vitro require an acclimatization process to ensure that a sufficient number of plants survive and grow vigorously when transferred to the soil. Thus, the objective of this work was to develop studies on the in vitro culture of zygotic embryos from freshly harvested seeds and aged seeds of Coffea arabica L., as well as the acclimatization of coffee seedlings produced from these seeds. Two studies were carried out, the first study evaluating the in vitro culture of freshly harvested coffee seeds or seeds that have undergone accelerated aging. The zygotic embryos were extracted from the seeds and placed in contact with MS medium and, after 60 and 120 days, the plants were evaluated by counting normal, abnormal and dead seedlings. In the second study, acclimatization tests were carried out on these seedlings grown in vitro. Two times of culture were evaluated for transplanting from the in vitro to the ex vitro phase (60 and 120 days), two substrates (Tropstrato and coconut fiber); two environments (growth chamber and greenhouse with fogging). To compare the results, plant height, stem diameter, number of leaves and chlorophyll content were evaluated. It was concluded that the in vitro germination of zygotic embryos from aged seeds was less than recently harvested, but it was still satisfactory with 86%. But there was no difference between the qualities of the seeds in terms of the number of normal seedlings. Plants that were transplanted at 60 days performed better than those transplanted at 120 days. The greenhouse environment with fogging was better for seedling growth, possibly due to higher radiation and temperature. The best substrate was coconut fiber, as it ensures better development for both freshly harvested seedlings and aged seedlings. It is possible to develop healthy seedlings from seeds with less viability, such as the aged ones used in this study.